High-level athletes' adjustment to major life and sport stressors: An investigation of adjustment disorder and coping mechanisms - Simons, C. (University of the Sunshine Coast, 2022)
The mental health of high-level athletes has received increased research attention over the past decade. Rates of mental illness in athletes are comparable to, or slightly higher than, the rates reported for same-aged general population samples. The experience of a major life or sport stressor (e.g. injury, relocation, relationship break-up) has been recognised as a risk factor for mental health issues such as depression and anxiety in athletes. The pressures of dealing with stressors such as career threatening injury, performance expectations and involuntary career termination may particularly increase high-level athletes` risk of mental health issues. Despite this, Adjustment Disorder (AjD), a mental health diagnosis directly concerned with maladjustment to one or multiple stressors, is virtually absent from the athlete mental health literature. Therefore, this thesis presents the first investigation into AjD in high-level athletes.